The Relationship between Nurses’ Mental health and Working Motivation - Raeissi, pooran; Raeissi, nahid; Shokouhandeh, leila (Advances in Nursing & Midwifery, 2015)
Background and aim: Psychologists believe that paying attention to nurses’ psychological health can increase their motivation for conducting their duties while are at work . The aim of this study was to determine the relationship between mental health of nurses and their motivation in doing their tasks in Ganjavian Dezfool Hospital Method and material his was a correlational study being done on Ganjavian Hospital’s nurses in city of Dezfool (N=240). The data were collected via a questionnaire. Nurses’ mental health was measured using GHQ28 and their job motivation, by Herzberg motivation questionnaire. GHQ28 had four non-psychotic dimensions (1-Somatization, 2- Anxiety And Sleep Disorder, 3- Social Dysfunction, and Depression). with 7 questions within each dimension. Spearman correlation was used to test the research hypothesis of this research. Findings: The findings revealed that the relationship between 1. Mental health and Nurses Job motivation (p = 0/0001, r = - 0/279) 2. Physical symptoms and Herzberg hygiene factor ( p < 0/01 , r = - 0/ 276 ) - 3. Anxiety and sleep disorders , and Herzberg hygiene factor ( p < 0/01 , r = - 0/ 272 ) , 4. Social function disorder , and Herzberg hygiene factor ( p < 0/01 , r = - 0/ 377 ) , 5. Depression, and Herzberg hygiene factor ( p < 0/01 , r = - 0/ 227 ) , 6. Physical symptoms, and Herzberg motivational factor ( P < 0/01 , r < - 0/ 244 ) 7. Anxiety and sleep disorders, and Herzberg motivational factor ( p < 0/01 , r = - 0/ 233 ) 8. Social function disorder, and Herzberg motivational factor ( p < 0/01 , r = - 0/ 286 ) 9. Depression, and Herzberg motivational factor (p < 0/01, r = - 0/ 227) are significant. Conclusion: The scores of nurses’ mental health and Job motivation are correlated in a positive way, thus investing on nurses’ mental health potentially enhance nurses’ job motivation at hospital. Keywords: Mental health, Nurse, Motivation, Hospital.